Review of plants with hepatoprotective activity evaluated in Mexico - Torres González, Liliana; Waksman de Torres, Noemí; Pérez Meseguer, Jonathan; Muñoz Espinosa, Linda Elsa; Salazar Aranda, Ricardo; Cordero Pérez, Paula (UANL. Facultad de Medicina, 2014)
Liver diseases represent a major health problem around the world. in Mexico these are the 5th leading cause of death in the economically active population. in Mexico, it is estimated that about 60% of the population uses some medicine from plants to treat their illnesses. The purpose of this work was to search for medicinal plants in Mexico that have been evaluated for their hepatoprotective effect in different models. in this review we found only 13 plants evaluated for hepatoprotective activity: Amole tuber, Cochlospermum vitifolium, Heterotheca inuloides, Hibiscus sabdariffa, Leucophyllum frutescens, Prostechea michuacana, Psidium Guajava, Rosmarinus officinalis, Verbena Carolin, Centaurea americana, Juglans mollis, Krameria ramossisima and Turnera diffusa. This study describes the studies conducted in Mexico for each of them and the international literature reports of pharmacological and phytochemical studies.